Persuasive Writing to Make Believe: Saints and Demons in the Golden Legend by James of Voragine - Silva Rocha, Tereza Renata (Eikón / Imago, 2017)
This work is dedicated to the persuasive elements in the text of the Golden Legend (1260-1298) written by the Dominican friar James of Voragine. It highlights the rhetorical use of elements of the marvelous —principally the performance of the Devil and the demons— in the text, with the intention of convincing the readers / listeners. It is a pedagogy about evil that reaches the laity through preaching, because the text of the Legend is an instrument used by the preachers to transmit the Christian teachings.